One‐Dimensional Epsilon‐Near‐Zero Crystals. Issue 7 (3rd June 2021) - Caligiuri, Vincenzo; Biffi, Giulia; Patra, Aniket; Pothuraju, Renuka Devi; De Luca, Antonio; Krahne, Roman
Abstract : Alternating multilayer architectures are an ideal framework to tailor the properties of light. In photonic crystals, dielectrics with different refractive indices are periodically arranged to provide a photonic bandgap. Herein, it is shown that a periodic arrangement of metal/insulator layers gives rise to an Epsilon‐Near‐Zero (ENZ) crystal with distinct bands of vanishing permittivity. The analogy of metal/insulator/metal (MIM) cavities to wave mechanics that describes them as quantum‐wells for photons is elaborated, and the Kronig–Penney (KP) model is applied to MIM multilayers. This KP modeling allows to extract the density of ENZ states, evidencing a significant increase at the band edges, which makes ENZ crystals appealing for lasing applications. The ENZ bandwidth can be tuned by the thickness of the metal layers and can span the entire visible range, and the interactions between bands of two different cavity subsystems in more complex ENZ crystals enable more elaborate ENZ band engineering. Finally, the difference between the ENZ crystals and hyperbolic metamaterials is elucidated and the conditions that separate these two regimes are quantified. The ENZ crystals constitute a new paradigm in the study of metal/insulator multilayers, and showcase a promising platform for light–matter interaction in photonic and plasmonic technologies. Abstract : Leveraging on the analogy between wave optics and wave mechanics, metal/dielectric multilayers are studied in the framework of solid‐state crystals, and the Kronig–Penney formalism is adopted to gain insights on the appearance of Epsilon‐Near‐Zero (ENZ) bands. This approach provides the density of ENZ states, the group velocity in the ENZ bands, and quantifies the boundary between ENZ crystals and hyperbolic metamaterials.